Analysis of PT RSI's Instagram Promotion Strategy Based on the AISAS Model - Rahmah, Fathiyah Nurshabrina; Murdowo, Djoko (PERSPEKTIF, 2025)
Instagram is widely used as a promotional medium by service companies, including PT Ravycool Sinergi Indonesia (PT RSI) which offers air conditioning cleaning services. However, the effectiveness of its promotion has not been optimized. This research analyzes PT RSI's Instagram promotion strategy using the AISAS model (Attention, Interest, Search, Action, Share). The method used is descriptive qualitative with a case study approach through observation of the @jasacuciacjakarta account, interviews, and analysis of Instagram Insights for the period August-October 2024. The results show a decrease in user engagement from the Attention stage (844 accounts) to Search (114 accounts), and only 5 accounts shared the content. The Action stage recorded 518 customers, but most of them were existing customers. The Share stages are the weak points of PT RSI's marketing strategy. It is recommended to strengthen educational content, Call to Action (CTA), and customer testimonials to increase promotional effectiveness.